IMPLEMENTASI PENDIDIKAN KARAKTER NILAI RELIGIUS PADA MATA PELAJARAN SEJARAH KELAS X IIS DI SMA MUHAMMADIYAH 1 PONTIANAK - Abdullah, Imam; Firmansyah, Andang; Firmansyah, Haris (Universitas Tanjungpura, 2025)
Thisresearch tries to analyze the implementation of religious character education in history subjects among Grade X IIS students at SMA Muhammadiyah 1 Pontianak. Religious character education is essential in shaping a generation that excels not only in knowledge and skills but also in moral integrity. The study takes a descriptive qualitative method, gathering data through observation, interviews, and recording. The findings reveal that history teachers have effectively designed and implemented learning activities based on religious values using lesson plans (RPP), while also cultivating religious habits among students, such as reciting the Qur